Cannabis sativa sp. as an adjunctive therapy in orofacial pain’s treatment: Narrative review (Research, Society and Development, 2023)
The plant Cannabis sativa sp. is known by its therapeutic potentials at least 5.000 year ago, as says the first humanity’s pharmacopoeia, the Pen-ts’ao ching. However, by the mid 60’s, USA’s neocolonial expansion used its proibition to be able to segregate native peoples (indigenous peoples and africans) who had it as part of their medicine and culture. In parallel with the proibition, evidence-based medicine was in charge of bringing to light results that corroborated the effectiveness of plant’s use in numerous pathologies. Many of these whose conventional treatments were scarce, in addition to being quite associated with side effects and therapeutic resistance. This has made Cannabis increasingly studied and used, including in dental patients, in an attempt to treat orofacial pain symptoms. Such pathology is directly linked to dentistry, encompassing painful conditions in the extra and intraoral region. In view of this, the objective of this work is to search for scientific articles, without time limit, which dealt with the use of formulations containing Cannabis extract in dentistry. Evidences are then presented to justify the possibility of its use by dental professionals, as a possible way to treat orofacial pain unresponsive to existing conventional treatments. The objective of this work is to search for scientific articles obtained from Google Scholar, Scientific Electronic Library (Scielo), PubMed and CAPES journals, without time limit, dealing with the use of formulations containing Cannabis extract in dentistry. Evidences are then presented to justify the possibility of its use by dental professionals, as a possible way to treat orofacial pain unresponsive to existing conventional treatments.